Post Disaster Psychiatric Disorder: A Case of Study of a Liberian Refuge Woman in Nigeria (1995)
Post-traumatic stress disorder (PTSD) is the latest classification of neurotic disorders emanating nom traumatic experiences (DSM III). It has been a focus of empirical interest among contemporary researchers. This interest has grown over the years as a result of concern for adequate intervention to victims of both natural disasters and deliberate human torture. The present study is a case report of a Liberian refugee woman in Nigeria who was referred for expert management. Efforts were made to systematically draw inference about how the process of trauma could devastatingly dispose an otherwise premorbidly stable individual to a state of psychiatric breakdown.